Exogenous Functional Mitochondria Derived from Bone Mesenchymal Stem Cells That Respond to ROS Can Rescue Neural Cells Following Ischemic Stroke - Dai L; Wu Z; Yin L; Cheng L; Zhou Q; Ding F (Dove Medical Press, 2024)
Lihua Dai,1,* Zheqian Wu,1,* Liili Yin,1 Longjian Cheng,1 Qiang Zhou,2 Fei Ding1 1Department of Emergency, Shidong Hospital, ShangHai, People's Republic of China; 2Department of General Surgery, Eighth People's Hospital, ShangHai, People's Republic of China*These authors contributed equally to this workCorrespondence: Fei Ding; Qiang Zhou, Email 10119038@qq.com; rabbit1264@163.comBackground: Upon uptake by stressed cells, functional mitochondria can perform their normal functions, ultimately enhancing the survival of host cells. However, despite the promising results of this approach, there is still a lack of understanding of the specific relationship between nerve cells and functional mitochondria.Methods: Functional mitochondria (F-Mito) were isolated from bone marrow-derived mesenchymal stem cells (BMSCs). The ability of microglia cells to internalize F-Mito was evaluated using a middle cerebral artery occlusion (MCAO) model in C57BL/6J mice and an oxygen-glucose deprivation/reoxygenation (OGD/R) cell model. After OGD/R and F-Mito treatment, the temporal dynamics of intracellular reactive oxygen species (ROS) levels were examined.The relationship between ROS levels and F-Mito uptake was assessed at the individual cell level using MitoSOX, Mitotracker, and HIF-1α labeling.Results: Our findings indicate that microglia cells exhibit enhanced mitochondrial uptake compared to astrocytes. Furthermore, internalized F-Mito reduced ROS levels and HIF-1α levels. Importantly, we found that the ROS response in microglia cells following ischemia is a critical regulator of F-Mito internalization, and promoting autophagy in microglia cells might reduce the uptake of ROS and HIF-1α levels.Conclusion: It is verified that F-Mito derived from BMSCs play a protective role in ischemia-reperfusion injury, as their weakening reduces microglial cell activation and alleviates neuroinflammation.Keywords: neuroinflammation, ROS, stem cell, HIF-1α, ischemic stroke